Serial electrocardiographic changes in healthy and stressed neonates. Issue 8 (August 1983) - Jedeikin, R; Primhak, A; Shennan, A T; Swyer, P R; Rowe, R D
Abstract : Serial changes in T-wave vector and polarity were assessed in 162 electrocardiograms, 117 from 44 healthy term neonates and 45 from 17 stressed neonates. Records were taken at 5 to 8 hours, 24 to 33 hours, and 71 to 96 hours after birth. Sequential changes in both T-wave amplitude and frontal and horizontal axes were found in both groups. A lag period was noted between healthy and stressed infants when comparing changes in T-wave amplitude, with greater flattening of T-waves for longer periods of time after birth in the stressed group. The normal changes in T-wave axis over time in the horizontal and frontal planes showed a similar lag in the stressed group. Alterations of T-wave amplitude and axis alone may be markers of myocardial ischaemia in neonates but are only reliable signs after the first 24 hours of life.